Anticardiolipin antibodies in ischaemic heart disease: marker or myth?. Issue 5 (May 1993) - Phadke, K V; Phillips, R A; Clarke, D T; Jones, M; Naish, P; Carson, P
Abstract : OBJECTIVES--To assess the incidence and significance of anticardiolipin antibodies after myocardial infarction and in unstable angina. DESIGN--A prospective study of all patients under 60 admitted to the coronary care unit over a 12 month period with a diagnosis of acute myocardial infarction who were followed up for a further 12 months. Patients admitted with unstable angina were similarly assessed but not followed up. Anticardiolipin antibody concentrations were compared with those of age matched controls. SETTING--A district general hospital. PATIENTS--307 patients with acute myocardial infarction and 160 patients with unstable angina. RESULTS--Anticardiolipin antibody concentrations in the two patient groups did not differ significantly from those in the control groups. Antibody concentrations were not related to a history of angina or myocardial infarction nor were they related to subsequent cardiovascular complications. CONCLUSION--This study shows no significant association between anticardiolipin antibody concentrations and either myocardial infarction or unstable angina.